Figurative Language and Its Emotional Impact in YOASOBI's The Book 1 Lyrics: A Semantic Approach - Yusri, Muh. Haizam; taqdir, Taqdir (Departemen Sastra Jepang, Fakultas Ilmu Budaya, Universitas Hasanuddin, 2025)
This study analyses the use of figurative language in The Book 1 album lyrics by YOASOBI through a semantic approach. Figurative language, including metaphor, personification, simile, and hyperbole, is crucial in enhancing song lyrics' emotional depth and artistic expression. This research explores how these figurative elements contribute to meaning-making and emotional engagement in the songs. A qualitative descriptive-analytical method focused on semantic analysis of selected lyrics. The data consist of seven songs from the album The Book 1, which were analysed through document analysis to identify patterns of figurative language. Each instance of metaphor, personification, simile, and hyperbole was categorized based on its linguistic structure and contextual function within the lyrics. The findings reveal that metaphors in YOASOBI’s lyrics establish strong symbolic imagery by connecting abstract concepts with concrete objects. Personification is used to attribute human qualities to non-human entities, intensifying emotional resonance. Simile explicitly compares two distinct elements to clarify feelings, while hyperbole amplifies emotions to create dramatic effects. These devices collectively enrich the meaning of the lyrics, allowing listeners to experience a deeper emotional connection to the songs. The study concludes that YOASOBI’s use of figurative language enhances their music's aesthetic and emotive aspects, making their lyrics more impactful and immersive.